Nicorandil, Gastrointestinal Adverse Drug Reactions and Ulcerations: A Systematic Review. Issue 3 (March 2016) - Pisano, Umberto; Deosaran, Jordanna; Leslie, Stephen; Rushworth, Gordon; Stewart, Derek; Ford, Ian; Watson, Angus
Abstract Introduction Nicorandil is a popular anti-anginal drug in Europe and Japan. Apart from some common adverse drug reactions (ADR), its safety is satisfactory. Several reports have suggested a link between nicorandil, gastrointestinal (GI) ulceration and fistulas. The review aims to critically appraise, synthesize and present the available evidence of all known GI ADR per anatomical location. Methods The study complied with the PRISMA statement. Literature and pharmacovigilance databases were used to provide rate and/or calculate parameters (median age, median dose, history of symptoms, length of therapy and healing time after withdrawal of the drug). Differences in distribution of quantitative variables were analyzed via Mann–Whitney test. Correlation between quantitative variables was assessed with a Spearman's correlation coefficient. Ap value <0.05 was significant. Results Oral ulcerations occur in 0.2% of the subjects, anal ulcerations are present between 0.07% and 0.37% of patients. Oral and distal GI involvements are the most common ADR (28–29% and 27–31% of all GI ADR, respectively). The hepatobiliary system, the pancreas and salivary glands are not affected by nicorandil exposure. The time to develop oral ulcerations is 74 weeks among people on <30 mg/day compared to only 7.5 weeks in individuals on higher regimens (p = 0.47). There is a significant correlation between dose and ulcer healing time (Spearman's 0.525, p < 0.001). Conclusions Ulcerative disease is a very commonly reported GI ADR. A delayed ulcerative tendency supports the hypothesis of an ulcerogenic metabolite. Nicorandil seems to act as a cause of the ulcerations, but appears to also work in synergy with other promoting factors. Whether the action of the metabolites relies on a specific mechanism or a simple chemical ulceration is still to be established.